SPECIFIC FEATURES OF SPEECH COMPETENCE OF FUTURE ENGLISH TEACHERS. - Aliboeva, Zarnigor (Журнал иностранных языков и лингвистики, 2021)
The formation of speech competence in future English teachers, its characteristic essence, as well as speech ability and skill, types of speech activities were discussed.